STOCK YIELDS, STOCK DIVIDENDS AND INFLATION. - Preinreich, Gabriel A. D. (The Accounting Review, 1932)
The yield of bonds has long been recognized as capable of mathematical determination, bond tables have long been in general use. The simplest ratio often called "yield" is obtained by dividing the annual dividend payments per share by the market value of a share. This ratio disregards corporate earnings, which may amount to more or less than the dividends paid. In the case of a bond it is well known that its present value is obtained by discounting each of the future payments promised on its face at the money rate prevailing at any given moment. The money rate, in this sense, is individual rather than general, that is, it includes a charge for risk dependent upon the merits of the bond. A bondholder earns a constant return on a constant capital, whereas a stockholder frequently obtains a more or less constant rate of return on an increasing capital, because a portion of the corporate earnings has been reinvested by the company. It is an important duty of the corporate management to formulate dividend policies which conform to these conditions.